APPLICATION OF LIQUID SMOKE FOR SMOKE FLAVORED FISH (Cryptopterus bicirchis) PROCESSING - Ade Novaria Siska; Tjipto Leksono; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was aimed to determine the good kinds of firewood as smoke liquid material for producing smoke flavored catfish (Cryproterus bicirchis) mostly preferred by consumers. The method used was experimental and composed as completely randomized design (CRD). The treatments were the used of different liquid smoke to produce smoke flavored catfish. The liquid smoke was pyrolyzed from different kinds of firewood, namely: laban wood (Vitex pubescens), rubber wood (Hevea brasiliensis), coconut shell (Cocos nucifera), and coconut fibers. The smoke flavored catfish produced were evaluated for the consumer preference assessed by hedonic test and the characteristic of physico- assessed for the content of moisture, total acid and total fenol, and the value of pH. The results showed that the best kind of firewood used for smoke material of liquid smoke was distilled laban wood because it had the highest score of aroma 7.7, existence 7.7, flavor 7.5, and texture 7.6 but not significantly different to those exposed on coconut shell. It was containing 0.8 ppm of total phenols, 0.4 % of total acid and pH value 6.2. Thus, the diminishing availability of laban wood in the nature could be replaced by the coconut shell as a biomass of agricultural waste.Keywords: coconut shell, Cryproterus bicirchis, laban wood, liquid smoke.